Effect of physical activity on the cardiometabolic profiles of non-obese and obese subjects: Results from the Korea National Health and Nutritional Examination Survey - An, Sang Joon; Jung, Mi-Hyang; Ihm, Sang-Hyun; Yang, Yun-jung; Youn, Ho-Joong (PloS one, 2019)
Physical inactivity is an important but often neglected risk factor for various cardiovascular diseases. We hypothesized that physical inactivity might have deleterious effects on metabolic health in obese and non-obese subjects. We evaluated the effect of physical activity on the cardiometabolic profiles of a nationwide cohort of non-obese and obese individuals who did not have overt cardiovascular diseases. A total of 3,830 study subjects were divided into two groups based on their body mass index (BMI). Within each BMI group, participants were divided according to their physical activity level. To ascertain their cardiometabolic profiles, we collected data regarding the homeostasis model assessment-estimated insulin resistance (HOMA-IR) index, high-density lipoprotein (HDL)-cholesterol level, systolic blood pressure, heart rate, and high-sensitivity C-reactive protein (hsCRP) level. Physically inactive subjects demonstrated markedly elevated HOMA-IR index and heart rates in each BMI category, even after adjustments for baseline covariates. They also tended to have worse profiles for HDL-cholesterol, systolic blood pressure, and hsCRP levels. A significant elevation in cardiometabolic risk was noted across the four physical activity/obesity groups (p<0.05). HOMA-IR index was largely affected by obesity, but within each BMI category, physical inactivity independently elevated the risk for worsening insulin resistance. In addition, physical inactivity significantly increased the risk of elevated heart rate in both non-obese and obese individuals. Notably, the detrimental effect of physical activity on heart rate was not modified by obesity. Physical activity was associated with favorable cardiometabolic risk profiles with regard to insulin resistance status and heart rate level in both BMI groups. Our results suggest that increasing physical activity could be a helpful strategy for improving the cardiometabolic health in the Korean population, regardless of obesity status.